Suprachoroidal injection of triamcinolone acetonide as adjuvant to surgical treatment of epiretinal membrane - Francesco Morescalchi; Federico Gandolfo; Vito Romano; Andrea Baldi; Francesco Semeraro (International Journal of Retina and Vitreous)
Abstract Background To analyse the effect of suprachoroidal injection (SChI) of triamcinolone acetonide (TA) on macular thickness (CRT), ectopic inner foveal layer thickness (EIFL-T) and best corrected visual acuity (BCVA) in pseudophakic patients undergoing vitrectomy for epiretinal membrane (iERM) compared to intravitreal injection of TA (IVTA). Methods Prospective matched comparison of patients undergoing vitrectomy for Govetto stage 3 and 4 iERM. 25 eyes receiving IVTA (G-1) were compared to 23 eyes receiving SChI-TA (G-2) during vitrectomy. Primary outcome was change in BCVA, CRT, EIFL-T before surgery and 1, 3 and 6 months after surgery. Secondary outcome was the incidence of cystoid macular edema (CME). Results Six months after surgery, G2 had a greater mean reduction in CRT (−222 µm vs −131 µm) and EIFL-T (−200 µm vs −104 µm) than G1. BCVA improved more in G2 than in G1 (p = 0.02). Foveal depression reformed in 43% of cases in G-2 and 16% of cases in G-1. Incidence of postoperative CME was 16% in G-1 and 4.3% in G-2. Conclusions During vitrectomy for iERM, SChI-TA was more effective than IVTA in reducing CRT and EIFL-T and improving BCVA. SChI-TA was effective in preventing postoperative CME. SChI-TA treatment was safe and reproducible and did not affect postoperative IOP. Trial registration NP6289—June 18th, 2024 (retrospectively registered).